Aplikasi Pemesanan Makanan pada Restoran 1953 Indonesia Berbasis Web - Farida Nurlaila (Jurnal Informatika Universitas Pamulang, 2019)
The restaurant business is one area that promises many benefits. But in some cases, not all restaurants can run their business smoothly. For example because of the lack of promotion of the types of food offered, the variety of menus presented for the customer service process is unsatisfactory. This research was directed to Restoran 1953 Indonesia, because the problems mentioned above were experienced by Restoran 1953 Indonesia. For this reason, a system is needed that can solve problems in the restaurant business today. That way, this application can facilitate customers in the ordering process and Restoran 1953 Indonesia in providing the best service.